A mathematical programming-based heuristic for the production routing problem with transshipments. (November 2020) - Avci, Mustafa; Topaloglu Yildiz, Seyda
Highlights: The production routing problem with transshipments is addressed. An MIP formulation and a mathematical programming-based heuristic are developed for its solution. The proposed heuristic provides high quality solutions for the problem instances. Abstract: The production routing problem (PRP) is a difficult optimization problem which arises in the planning of integrated supply chains. The purpose of solving the PRP is the simultaneous optimization of the production, inventory, distribution, and routing decisions, which typically appears in vendor managed inventory systems. In this study, the classical PRP is extended by considering transshipments, either from supplier to retailers or between retailers, to further reduce the total cost. A mathematical programming-based heuristic is proposed to solve the problem. The algorithm is applied to two sets of randomly generated problem instances. The computational results show that the proposed approach is effective in solving the problem. Moreover, we conduct extensive numerical experiments to analyze the impact of the transshipments on the overall system.